Entrepreneurial Training and Entrepreneurial Intentions: A Mediated Mediation Analysis of Entrepreneurial Self-efficacy and Attitude of Undergraduate Finalists in Uganda - Kisubi, Moses Kisame; Korir, Michael (SEISENSE Journal of Management, 2021)
Purpose – The purpose of this paper is to determine whether the association between Entrepreneurial Training and Entrepreneurial Intentions is mediated by (1) Entrepreneurial Self-Efficacy, (2) Entrepreneurial Attitude, and (3) whether the first mediation is further mediated by Entrepreneurial Attitude. Design – to attain the study objectives, a cross-sectional and explanatory survey approach was employed. Systematic sampling technique was utilized to collect data from a sample of 458 final-year undergraduate students from two Ugandan public universities. Results – a significant partial mediation effect of Entrepreneurial Self-Efficacy and Entrepreneurial Attitude between Entrepreneurship Training and Entrepreneurial Intentions was established and a mediated mediation effect. Implications – the study provides maiden evidence that Entrepreneurial Training and Entrepreneurial Intentions are significantly and serially mediated by Entrepreneurial Self-Efficacy and Entrepreneurial Attitude. Managers and policymakers may use this study results to further student’s entrepreneurial competencies. Society may also use our results to support entrepreneurial ventures as a vehicle for creating jobs for graduates Originality/value – the novelty of this paper is threefold; it provides evidence on the mediating role of; (1) entrepreneurial self-efficacy, (2) entrepreneurial attitude, and (3) we provide initial evidence on the mediated mediation effect of Entrepreneurial Self-Efficacy and Attitude in the relationship between Entrepreneurial Training and Entrepreneurial Intentions.